(untitled) - Sturge, Ernest Adolphus (Tokyo, 1905)
Honorary member of the imperial educational society of Japan
Keywords: Giáo dục thể chất và huấn luyện,Nhật Bản,Physical education and training,Japan; Đời sống xã hội và phong tục,Social life and customs; Nhật Bản,Japan